Identificação de ectoparasitos monogenéticos em serra spanish mackerel - Silva, Cláudio Giovanio da (Universidade Federal Rural do Semi-Árido, 2017)
Serra Mackerel (Scomberomonus brasiliensis) is a fast, pelagic species, distributed from the western Atlantic Ocean and the Caribbean Sea, the Yucatan Peninsula and Belize to Rio Grande do Sul in Brazil. Fish have the highest parasite infestation rates among vertebrates and these parasites are part of all ecosystems. The objective of this work was to carry out the taxonomic identification of monogenetic parasites conditioned in the laboratory from previous research. Between 2009 and 2017, 298 Scomberomorus brasiliensis fish were collected and analyzed in Rio Grande do Norte. A total of 48 parasites were distributed in three families: 31 from the Thoracocotylidae family of the species Scomberocotyle scomberomori in the gills, 12 Axinidae of the species Allopseudaxine macrova in the gills and 05 Mazocraeidae of the species Kuhnia scombri in the gills. In this study a new host was identified for the three species identified, with the first occurrence of the monogenetic parasites S. scomberomori, A. macrova and K. scombri in a new host S. brasiliensis presenting low parasitic ecological indices (prevalence, mean intensity, abundance mean) for the three species.
Monografia
Keywords: Peixes parasitado; Peixes marinhos; Parasitismo; Monogenea em Scombridae; Parasited fish; Marine fish; Parasitism; Monogenea in Scombridae; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA